1983
DOI: 10.1111/j.1365-2672.1983.tb02637.x
|View full text |Cite
|
Sign up to set email alerts
|

The bactericidal, fungicidal and sporicidal properties of hydrogen peroxide and peracetic acid

Abstract: The antimicrobial properties of aqueous solutions of peracetic acid and hydrogen peroxide have been compared. Peracetic acid exhibited excellent antimicrobial properties, especially under acidic conditions. Reductions by a factor of 10(6) in the numbers of vegetative bacteria are obtained within 1 min at 25 degrees C using a solution containing 1.3 mmol/l of peracetic acid. Rapid activity against bacterial spores and yeasts also occurs. Hydrogen peroxide is more effective as a sporicide than as a bactericide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
154
0
17

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(174 citation statements)
references
References 12 publications
3
154
0
17
Order By: Relevance
“…Baldry (1983) exposed S. cerevisiae to different concentrations of PAA, however different temperatures and pH were used (5.0, 6.5 and 8.0), versus our experiment, where pH was not a factor to control since only deionized water was used to prepare the PAA solutions that were added to the flasks (in vitro experiments) and where temperature was stable during the whole time of our experiment. Baldry (1983) found that the efficacy of PAA against two strains of S. cerevisiae decreases with increasing pH, since when alkalinity of the solution increases, peracetic acid is hydrolyzed to form acetic acid and hydrogen peroxide (Yuan et al, 1997). Accordingly, Baldry (1983) found that resistance among genera (particularly between Z. bailii and S. cerevisiae) is variable, this latter aspect also found in our experiments.…”
Section: In Vitro Reduction Of Yeastsupporting
confidence: 80%
See 2 more Smart Citations
“…Baldry (1983) exposed S. cerevisiae to different concentrations of PAA, however different temperatures and pH were used (5.0, 6.5 and 8.0), versus our experiment, where pH was not a factor to control since only deionized water was used to prepare the PAA solutions that were added to the flasks (in vitro experiments) and where temperature was stable during the whole time of our experiment. Baldry (1983) found that the efficacy of PAA against two strains of S. cerevisiae decreases with increasing pH, since when alkalinity of the solution increases, peracetic acid is hydrolyzed to form acetic acid and hydrogen peroxide (Yuan et al, 1997). Accordingly, Baldry (1983) found that resistance among genera (particularly between Z. bailii and S. cerevisiae) is variable, this latter aspect also found in our experiments.…”
Section: In Vitro Reduction Of Yeastsupporting
confidence: 80%
“…Baldry (1983) found that the efficacy of PAA against two strains of S. cerevisiae decreases with increasing pH, since when alkalinity of the solution increases, peracetic acid is hydrolyzed to form acetic acid and hydrogen peroxide (Yuan et al, 1997). Accordingly, Baldry (1983) found that resistance among genera (particularly between Z. bailii and S. cerevisiae) is variable, this latter aspect also found in our experiments. However, as we found resistance is also variable among strains.…”
Section: In Vitro Reduction Of Yeastsupporting
confidence: 80%
See 1 more Smart Citation
“…Hydrogen peroxide is an oxidizing agent capable of transforming numerous organic molecules (Petri et al 2011). It has been documented that this compound exhibits antibacterial and antifungal properties (Baldry 1983). There are several studies concerning the antifungal activity of biocides based on silver ions and hydrogen peroxide (Tasić 2009, Abdel-Mageed et al 2012) but, to our knowledge, very few regarding Aspergillus species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Devido às suas propriedades bactericidas, virucidas, fungicidas e esporicidas, seu uso como desinfetante de esgoto doméstico recebe cada vez mais atenção (Baldry, 1982;Baldry & French, 1989;Alasri et al, 1992;Sanchez-Ruiz et al, 1995;Gasi et al, 1995;Rajala-Mustonen et al, 1997;Block, 2001). Outras vantagens do ácido peracético como desinfetante de efluentes são: facilidade de implementação de tratamento (sem a necessidade de elevado investimento), largo espectro de atividade mesmo na presença de matéria orgânica heterogênea, ausência de residual ou subprodutos tóxicos e/ou mutagênicos, desnecessária descloração, baixa dependên-cia do pH e curto tempo de contato.…”
Section: Introductionunclassified